IMPLEMENTASI BAHAN AJAR ANIMASI SEBAGAI INOVASI PEMBELAJARAN DI MTsS IHYAUSSUNNAH - Nasrullah, Syihan Elfayza (Journal of Contemporary Indonesian Islam, 2025)
The use of animation in teaching materials is a strategic innovation in 21st century education, especially to increase the effectiveness of learning in the digital era. This research describes the implementation and impact of animation-based teaching materials in PAI learning at MTsS Ihyaussunnah with a descriptive qualitative approach through observation, interviews and documentation. Results show animation is able to bridge theory and practice through interactive visualizations that increase students' understanding, interest and motivation. ADDIE model-based development has proven to be systematic, from needs analysis to classroom evaluation. Animation also supports understanding abstract concepts as well as strengthening Islamic values. The main obstacle is the limited infrastructure and digital literacy of teachers, which can be overcome with training and institutional support. In general, animative teaching materials are considered valid, practical and relevant to the digital generation, and have the potential to be integrated into educational policies to support independent curricula and digital transformation.